2020
DOI: 10.3390/metabo10040139
|View full text |Cite
|
Sign up to set email alerts
|

A Multivariate Metabolomics Method for Estimating Platelet Mitochondrial Oxygen Consumption Rates in Patients with Sepsis

Abstract: Background: Sepsis-induced alterations in mitochondrial function contribute to organ dysfunction and mortality. Measuring mitochondrial function in vital organs is neither feasible nor practical, highlighting the need for non-invasive approaches. Mitochondrial function may be reflected in the concentrations of metabolites found in platelets and whole blood (WB) samples. We proposed to use these as alternates to indirectly estimate platelet mitochondrial oxygen consumption rate (mOCR) in sepsis patients. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…This finding could be met with surprise since published studies indicate that the PDH complex is inhibited during sepsis, resulting in a switch from mitochondrial aerobic oxidation to cytoplasmic anaerobic glycolysis, a process known to contribute to the formation of lactic acid and intracellular acidosis, which can lead to intracellular Ca2 + overload, mitochondrial membrane damage [ 58 , 82 , 83 ]. Nevertheless, contrasting the general PDC-dependent metabolic reprogramming response in sepsis [ 58 , 84 , 85 ], several studies demonstrated that mitochondrial oxygen consumption in PLTs is increased in septic patients, and closely related to their survival rate [ 86 , 87 , 88 ]. Therefore, based on our observations, we speculate that due to its chaperone and potential shuttling function, NAP1L1 protein in septic PLTs could help stabilize the conformation of PDC-E2 molecules, and also mediate the known one-way transport [ 89 ] into the mitochondrial compartment.…”
Section: Discussionmentioning
confidence: 99%
“…This finding could be met with surprise since published studies indicate that the PDH complex is inhibited during sepsis, resulting in a switch from mitochondrial aerobic oxidation to cytoplasmic anaerobic glycolysis, a process known to contribute to the formation of lactic acid and intracellular acidosis, which can lead to intracellular Ca2 + overload, mitochondrial membrane damage [ 58 , 82 , 83 ]. Nevertheless, contrasting the general PDC-dependent metabolic reprogramming response in sepsis [ 58 , 84 , 85 ], several studies demonstrated that mitochondrial oxygen consumption in PLTs is increased in septic patients, and closely related to their survival rate [ 86 , 87 , 88 ]. Therefore, based on our observations, we speculate that due to its chaperone and potential shuttling function, NAP1L1 protein in septic PLTs could help stabilize the conformation of PDC-E2 molecules, and also mediate the known one-way transport [ 89 ] into the mitochondrial compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of functional PLT activity in these cases could help the prophylaxis of anticoagulant treatment and improve the patients’ quality of life. Therefore, analysis of mitochondrial respiration of PLT represents a promising approach [ 38 , 39 , 40 , 41 , 42 ]. Increased respiration of PLT isolated from the blood of septic patients correlates with activation of circulating proinflammatory cytokines [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peaks were assigned to metabolites with Chenomx NMR Suite 9.0 (Chenomx, Edmonton, Alberta, Canada) and previous publications [ 18–22 ] ( Figure 1 ). Peak amplitudes were considered to reflect metabolite concentrations, and z-scores of metabolites with VIP > 1 were used for pathway analysis in MetaboAnalyst 5.0 ( www.metaboanalyst.ca ), using the Kyoto Encyclopedia of Genes and Genomes (KEGG) as pathway library [ 23 ].…”
Section: Methodsmentioning
confidence: 99%